Contribution to the Security of the Information System - A. Ben Charke; M. Chabi; M. Fakir (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Security of information systems has become a critical problem of companies. In this paper, the principles of security and the description of some attacks that threatening the information system are given. After Techniques of cryptography, digital signature to ensure the confidentiality, integrity and authentication of data, are described. Some security protocol such as Secure Shell (SSH), Secure Socket Layer (SSL), Internet Protocol SECure (IPSEC), in order to ensure the security of connection resources, are described. Intrusion detection is implemented using free IDS "SNORT" software.